Psychosocial Resources and Quality of Life in Transgender Women following Gender-Affirming Surgery. Issue 10 (1st October 2019) - Breidenstein, Anja; Hess, Jochen; Hadaschik, Boris; Teufel, Martin; Tagay, Sefik
Abstract: Introduction: Psychosocial resources like social support or intrapersonal coping skills play an important role in resilience and quality of life (QOL), yet research systematically investigating the availability of different resources and QOL in transgender (trans) women is missing. Aim: The present study aimed to systematically investigate the existence of different psychosocial resources and QOL in trans women following gender-affirming surgery (GAS). Methods: Using a cross-sectional design, 557 trans women who had received GAS at the local urological department were invited to study participation. Criteria for study inclusion were 18 years and older, diagnosis of transsexualism according to the International Classification of Disease, completion of all sessions of GAS, and given written informed consent to study participation. Main Outcome Measures: Psychosocial resources were assessed using the Essen Resource Inventory (ERI), the Sense of Coherence Scale, and the Social Support Scale. QOL was assessed with the Short Form Health Survey. Data from trans women were compared to normative data of healthy non-trans women as reported in the respective test manuals. Results: In total, 158 trans women responded and participated in this study. They had received GAS 4 months to 21 years ago. The total sample was divided into 3 subgroups depending on the time interval since the participants' last GAS procedure (group 1: GAS 0.3−3 years ago (n = 48); group 2: GAS 3.1−10 years ago (n = 62); and group 3: GAS 10.1−21 years ago (n = 41)). Trans women retrospectively indicated their available resources 3 years ago (ERI 3-years) and in the last 4 weeks (ERI 4-weeks). Trans women who had received GAS within the last 3 years (group 1) showed an increase in resources when comparing ERI 3-year scores (presurgery) with ERI 4-week scores (postsurgery). No differences emerged for group 2 and group 3. Compared to normative data from non-trans women, trans women scored significantly lower on the ERI but not in measures of Social Support Scale or Sense of Coherence Scale. Compared to non-trans women, mental QOL was significantly impaired in trans women, whereas no differences in physical QOL emerged. Clinical Implications: As this study hints towards reduced psychosocial resources in trans women, the offering of specialized counseling can have high beneficial potential to support the development of resources, thereby enhancing QOL. Strength & Limitations: Data of a large sample of trans women is provided who were investigated up to 21 years after GAS. The study is limited by its cross-sectional design and the response rate of 42%. Conclusion: This study indicates that psychosocial resources improve around the time of GAS and seem to be improved and sustained in later years following GAS. Still, compared to non-trans women, trans women have a lower availability of resources and a lower mental QOL.